The Glycerophosphoinositols: From Lipid Metabolites to Modulators of T-Cell Signaling - Patrussi, Laura; Mariggiò, Stefania; Corda, Daniela; Baldari, Cosima T. (Frontiers in Immunology, 2013)
Glycerophosphoinositols (GPIs) are bioactive, diffusible phosphoinositide metabolites of phospholipase A2 that act both intracellularly and in a paracrine fashion following their uptake by specific transporters. The most representative compound, glycerophosphoinositol (GroPIns), is a ubiquitous component of eukaryotic cells that participates in central processes, including cell proliferation and survival. Moreover, glycerophosphoinositol 4-phosphate (GroPIns4P) controls actin dynamics in several cell systems by regulating Rho GTPases. Recently, immune cells have emerged as targets of the biological activities of the GPIs. We have shown that exogenous GroPIns4P enhances CXCL12-induced T-cell chemotaxis through activation of the kinase Lck in a cAMP/PKA-dependent manner. While highlighting the potential of GroPIns4P as an immunomodulator, this finding raises questions on the role of endogenously produced GroPIns4P as well as of other GPIs in the regulation of the adaptive immune responses under homeostatic and pathological settings. Here we will summarize our current understanding of the biological activities of the GPIs, with a focus on lymphocytes, highlighting open questions and potential developments in this promising new area.